A prospective study concerning the effect of pharmaceutical care services on patients with heart failure - Taner, Neda; Berk, Barkın (Marmara University, 2022)
Objective: Heart failure (HF), caused by an abnormality in cardiac function, is the inability of heart tissue to pump blood or deliver sufficient oxygen, resulting in abnormal diastolic volume. Drug-Related Problems (DRPs) can cause significant but preventable morbidity and mortality once specific medication errors and their contributing factors are identified. The aim of this prospective study is to determine the effect of pharmaceutical care in patients with heart failure in a Turkish hospital. Methods: A total of 160 patients with heart failure (80 patients in the control group, 80 patients in the intervention group) were examined at a university hospital. The results of the Pharmaceutical Care Survey were evaluated in accordance with the objective of the study. In addition, using the Pharmaceutical Care Network Europe (PCNE) classification system V8.01, the role and importance of the clinical pharmacist in identifying, preventing and resolving drug-related problems encountered during the treatment of two groups was assessed. The number and causes of potential DRPs were taken into scrutiny. Results: Comparing the results of the Pharmaceutical Care Survey in both groups at the end of the 6th month, the study group shows a significant improvement in the rates of "forgetting to take medication" (2.9%) and "experiencing any side effects from your drug" (4.5%). Compared to other problems, ineffectiveness of the drugs used in treatment was reported as the most common drug-related problem (n=23; 28.7%) in the study group (p<.05). 72.5% of the proposed interventions were accepted and the problem was found to be resolved in 31% of the patients. Conclusion: In this study, it is discussed that clinical pharmacists can play an active role in resolving DRPs in heart failure patients. It is therefore can be predicted that the training of information and warnings conveyed by the clinical pharmacist to the intervention group will make a significant contribution to the health of the patient within the framework of pharmaceutical care.
Keywords: Clinical Pharmacy; Drug-Related Problem; Heart Failure; Pharmaceutical Care